Investigation of the index case herd and identification of the genotypes of Theileria orientalis associated with outbreaks of bovine anaemia in New Zealand in 2012. Issue 1 (2nd January 2016) - Pulford, DJ; McFadden, AMJ; Hamilton, JS; Donald, J
Abstract: CASE HISTORY AND CLINICAL FINDINGS: On 7 September 2012 the Ministry for Primary Industries was notified of a dairy cow with regenerative anaemia (haematocrit (HCT) 0.08 L/L) in a herd of 465 Jersey-Friesian cross cows (index case herd) in the Northland region of New Zealand. Organisms consistent with Theileria spp. were present in red blood cells on a blood smear. No other causes of anaemia were detected following examination of affected cows. Blood samples collected from 29 randomly selected cows on 26 September 2012 showed that 24 (83%) were anaemic (HCT≤0.24 L/L) and therefore fitted the case definition for bovine anaemia associated with Theileria orientalis infection. LABORATORY FINDINGS: Using a T. orientalis type-specific PCR assay that targeted the single subunit rRNA gene, all of six animals tested were positive for T. orientalis type Ikeda. Blood samples collected from clinically affected cattle in 11 subsequent outbreaks from throughout the North Island showed that T. orientalis Ikeda type was a common finding, but mixed infections with Chitose type were also identified. In addition, using a PCR assay that targeted the major piroplasm surface gene, T. orientalis type 5 was detected in one cow from the Waikato region. DIAGNOSIS: The presence of T. orientalis type Ikeda, as well as type 5, was confirmed in cattle from outbreaks of bovine anaemia in herds throughout the North Island of New Zealand. CLINICAL RELEVANCE: Two new types of T. orientalis were identified in this investigation, that were associated with a sudden rise in cases of bovine anaemia. The body of evidence showed that the Ikeda type was implicated as the cause of disease observed in this epidemic.